The Contribution of Anharul–U-Loom in Overcoming The Problem of Drug Addicts in Klong Kam, Krabi, Thailand - Abdulloh Salaeh; Adnan Mohamed Yusoff; Shumsudin Yabi; Mohd Zohdi Mohd Amin; Norhasnira Ibrahim; Syed Najihuddin Syed Hassan (Human Resource Management Academic Research Society, 2024)
Indexed by ERA